Ratio of Local to Systemic Chemokine Concentrations Regulates Neutrophil Recruitment - Call, Douglas Ruben (American Society for Investigative Pathology, 2001)
CXC chemokines are important regulators of local neutrophil recruitment. In this study, we examined the role of the ratio of local to systemic chemokine concentrations as a significant factor determining local neutrophil recruitment. Thioglycollate was injected intraperitoneally into BALB/c mice resulting in a dose-dependent increase in neutrophil recruitment and local inflammation, as measured by peritoneal levels of interleukin 6. At the high dose of 3% thioglycollate, antibody inhibition of the murine chemokines KC and macrophage inflammatory protein-2 caused a reduction in peritoneal neutrophil recruitment by as much as 93%. A paradoxical effect was observed with a 0.3% thioglycollate intraperitoneal challenge. In this situation, inhibition of KC resulted in a significant increase in peritoneal neutrophils, and inhibition of macrophage inflammatory protein-2 also resulted in increased peritoneal neutrophils. These results were consistent with a reverse chemotactic gradient as described by the ratio of peritoneal to plasma KC levels. A higher ratio (ie, increased peritoneal chemokines compared to plasma) resulted in increased neutrophil recruitment after either the 3% or 0.3% thioglycollate challenge. Our results demonstrate that whereas sufficient local concentrations of chemokines are necessary, a critical factor dictating local neutrophil recruitment is the ratio of the local to the systemic chemokine concentrations.